Revealing the genetic basis of coat color in Tibetan sheep through selective sweep and transcriptomic analyses - Li, Xue; Han, Buying; Tian, Dehong; Liu, Dehui; Ma, Wulong; Bao, Guangcai; Wang, Lei; Pei, Quanbang; Zhang, Zian; Zhao, Kai (Frontiers in Veterinary Science, 2025)
Background and objectiveCoat color is an important economic trait in animal husbandry and plays a crucial role in the adaptability of animal. As a key economic trait in high-altitude areas, the genetic mechanisms regulating coat color in Tibetan sheep are not fully understood.MethodsIn order to explore the genetic basis of coat color in Tibetan sheep, this study focused on white-coated Plateau Tibetan sheep (PT) and black-coated Guinan black fur sheep (GB). Using whole genome sequencing (10× coverage), transcriptomic analysis, Sanger sequencing, and protein structure prediction to identify candidate genes and molecular markers associated with coat color.ResultsIn this study, a total of 9.28 million SNPs were annotated from whole-genome sequencing. Compared with the white-coated PT sheep, the skin transcriptome of black-coated GB sheep exhibited 659 up-regulated and 426 down-regulated genes. MC1R, MITF, and KIT were identified as candidate genes for the coat color of Tibetan sheep. Through Sanger sequencing of all exons of these genes and association analysis with coat color phenotypes, we found that 8 of 12 SNPs were significantly associated with coat color in Tibetan sheep. The coat color of individuals with heterozygous or homozygous mutations in both SNPs (rs3508196008 and rs409651063) in the MC1R gene were black. These two SNPs were likely to not cause loss or alteration of protein function, but rather affected the coat color of Tibetan sheep by regulating gene transcription and expression levels, and can be applied as molecular markers to regulate coat color in Tibetan sheep.ConclusionTwo molecular markers (rs3508196008 and rs409651063) in the MC1R gene regulating Tibetan coat color were identified through selective sweep analysis, transcriptome, Sanger sequencing, and the genetic mechanism of coat color was analyzed, which provided new insights for the genetics of coat color in Tibetan sheep, and provided effective markers and technical support for molecular breeding.